Papua New Guinea : Poverty and Access to Public Services - World Bank (Washington, DC, 2013)
This report analyzes the distribution of income, constructs a poverty profile, and looks at the extent to which the poor have access to basic services in Papua New Guinea. The analysis is based on data collected during a national household survey in 1996, and, data on a range of socioeconomic indicators, were collected nationally among urban, and rural households, within the country's five major regions. This shows that the distribution of consumption is highly uneven, since real per capita consumption level is over eight times higher than the poorest quartile, with marked disparities in consumption levels. A detailed review on the distribution of access to basic services, such as education, health care, rural infrastructure, and utilities is presented, suggesting the unequal access to these services further accentuates the effects of unequal income distribution. The county's safety net system is examined, revealing this system allows for income transfers from members of a particular "wantok" - informal network based on ethnicity, language, etc. - to needy members of the same wantok. Although this system adapted relatively well to changing socioeconomic environments, it does not appear to improve income distribution in rural areas. Finally, the report concludes that to effectively alleviate poverty, additional analysis needs to be undertaken, to include the factors which hinder productivity, and income.